Comparative analysis of two proposed models of connecting rods for crank-rocker engines using finite element method - Mohammed, S.E. (EDP Sciences, 2014)
In this study, static load analysis was performed on two proposed models of connecting rods (conventional and Y-shape con-rod) intended for use in the crank-rocker engine. The analysis was done by modeling the model using CATIA V5 software which was then analyzed using ANSYS Workbench 14.0 software. A static analysis was done to determine the von-misses stresses under tensile and compressive loading conditions. Two cases were studied, firstly, the load was applied at the rocker pin end and fixed at the crank end as a compressive load, and secondly, the load was applied at the same position as a tensile load with both cases under the same constant load. It was found from the analysis that the conventional connecting rod has yielded lower stress values for both cases as compared to the Y-shaped connecting rod. Based on the results, it was concluded that the normal connecting rod is better to be used for the crank-rocker engine. Â© 2014 Owned by the authors, published by EDP Sciences.